2021
DOI: 10.3390/pathogens10091140
|View full text |Cite
|
Sign up to set email alerts
|

Is Chlamydia to Blame for Koala Reproductive Cysts?

Abstract: A significant threat to koala populations is infection from Chlamydia, which results in disease and death. Wild koalas with Chlamydia infections are admitted to wildlife hospitals and treated with antibiotics; however, up to 50% of koalas that present to wildlife hospitals do not survive. A major contributor to high mortality is the development of reproductive cysts, resulting in female infertility and euthanasia. However, the diagnosis of reproductive disease is limited to ultrasound with no further investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Phillips and colleagues noted a considerable knowledge gap regarding the aetiology and pathogenesis of reproductive cysts because the diagnostic work-up is often limited to ultrasound scans. The authors concluded that further investigations are urgently needed to improve treatment of Chlamydia -infected koalas and to reduce these high mortality rates [ 16 ].…”
Section: Chlamydial Infections In Wildlife: Concerns For Spill-over A...mentioning
confidence: 99%
“…Phillips and colleagues noted a considerable knowledge gap regarding the aetiology and pathogenesis of reproductive cysts because the diagnostic work-up is often limited to ultrasound scans. The authors concluded that further investigations are urgently needed to improve treatment of Chlamydia -infected koalas and to reduce these high mortality rates [ 16 ].…”
Section: Chlamydial Infections In Wildlife: Concerns For Spill-over A...mentioning
confidence: 99%